2014
DOI: 10.1038/hdy.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding within human Schistosoma mansoni: do host-specific factors shape the genetic composition of parasite populations?

Abstract: The size, structure and distribution of host populations are key determinants of the genetic composition of parasite populations. Despite the evolutionary and epidemiological merits, there has been little consideration of how host heterogeneities affect the evolutionary trajectories of parasite populations. We assessed the genetic composition of natural populations of the parasite Schistosoma mansoni in northern Senegal. A total of 1346 parasites were collected from 14 snail and 57 human hosts within three vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 51 publications
4
40
1
Order By: Relevance
“…Data from T. minor, which appear to be relatively free of null alleles, suggest that inbreeding levels vary widely by louse infrapopulation, perhaps because initial host colonization is a relatively unpredictable process involving small numbers of parasites in some cases and larger numbers in others. Such variability in inbreeding level among parasite infrapopulations was observed in tapeworms and schistosomes, which also showed high levels of inbreeding in some infrapopulations and little or none in others ( Stefka et al 2009;Van den Broeck et al 2014). Nadler et al (1990) suggested that founder events at initial host colonization and the seasonal population bottlenecks in louse populations observed by Rust (1974) both can serve to decrease genetic diversity in chewing lice as compared to other insect species.…”
Section: Tests Of Louse Movement Within and Among Localitiesmentioning
confidence: 86%
“…Data from T. minor, which appear to be relatively free of null alleles, suggest that inbreeding levels vary widely by louse infrapopulation, perhaps because initial host colonization is a relatively unpredictable process involving small numbers of parasites in some cases and larger numbers in others. Such variability in inbreeding level among parasite infrapopulations was observed in tapeworms and schistosomes, which also showed high levels of inbreeding in some infrapopulations and little or none in others ( Stefka et al 2009;Van den Broeck et al 2014). Nadler et al (1990) suggested that founder events at initial host colonization and the seasonal population bottlenecks in louse populations observed by Rust (1974) both can serve to decrease genetic diversity in chewing lice as compared to other insect species.…”
Section: Tests Of Louse Movement Within and Among Localitiesmentioning
confidence: 86%
“…The genetic subdivision of parasites into infrapopulations has been shown to result in highly inbred populations of some animal parasites (Criscione et al, 2005; Van den Broeck et al, 2014). Nevertheless, unlike animal endoparasites, these plant species reproduce outside of the host, with carrion fly pollinators transporting pollen among flowers on different hosts due to both visual and olfactory attractants (Beaman et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…A common explanation is that parasite genetic diversity decreases with age because of stronger selection by the maturing host immunity (Bendixen et al 2001). Indeed, we found a negative correlation between the genetic diversity of blood parasites and the strength of the humoral response, but also a weak increase of parasite diversity with host age, indicating that older nestlings may increasingly act as a ''mixing bowl'' for different parasite strains (Van den Broeck et al 2014). Since more diverse infections may limit the potential of the immune system to react to novel antigens, the direction of a possible dependence remains to be established experimentally.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, the genetic diversity of parasites may decrease with the strength of the host immune response and host age as a correlate of the former (Ntoumi et al 1995;Van den Broeck et al 2014). Since plumage morph is a predictor of prevalence, parasitemia and parasite diversity in buzzards (Chakarov et al 2008(Chakarov et al , 2015a, and the humoral response is the most probable intermediate link between morph and infection measures, we predicted that (3) the antibody titres will negatively correlate with infection prevalence, parasitemia and parasite genetic diversity.…”
Section: Introductionmentioning
confidence: 99%